Reliability of Evidence to Guide Decision-Making in the Use of Acupuncture for Postpartum Depression - Hu, Xiuwu; Fan, Qian; Ma, Li; Jin, Rui; Gong, Rui; Zhao, Xiaoying; Qiu, Fenfen; Zhou, Liang (Frontiers in Public Health, 2022)
Background There is conflicting evidence on the effectiveness of acupuncture in the treatment of postpartum depression (PPD). This study aimed to assess previous systematic reviews/meta-analyses (SRs/MAs) on the effectiveness of acupuncture to treat PPD. Method SRs/MAs regarding the use of acupuncture for PPD were identified from the establishment of digital databases to November 2021. The Assessing the Methodological Quality of Systematic Reviews 2 (AMSTAR-2) was applied to evaluate the methodological quality of included SRs/MAs. The Grades of Recommendations, Assessment, Development and Evaluation (GRADE) was utilized to evaluate the evidence quality for outcomes of interest. Results Six studies that conducted quantitative syntheses were included. According to AMSTAR-2, the methodological quality of these SRs/MAs was critically low owing to limitations of items 2, 4, and 7. According to GRADE, no study included high-quality evidence and most studies included low-quality evidence. Conclusions Acupuncture m be beneficial for PPD, however, due to limitations of current evidence and inconsistent findings, further studies are needed to provide stronger evidence to draw definitive conclusions.